2022
DOI: 10.3390/dj10100188
|View full text |Cite
|
Sign up to set email alerts
|

Challenges and Opportunities for Dental Education from COVID-19

Abstract: With the ongoing COVID-19 pandemic, dental education has been profoundly affected by this crisis. First of all, COVID-19 brought physical and psychological health problems to dental students and educators. In addition, both non-clinical teaching and clinical-based training experienced challenges, ranging from fully online educational content to limited dental training, students’ research was delayed in achieving project milestones and there was hesitancy in respect of the COVID-19 vaccine. On the other hand, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 68 publications
0
3
0
Order By: Relevance
“…Given the pluses and minuses of the online/remote didactic activities, the majority (75%) of the participants in this study expressed their belief that the future of dental education will be impacted by the COVID-19 crisis. This is a general belief that has been revealed by many studies [ 9 , 10 , 12 , 23 , 29 , 36 , 42 , 44 , 45 , 46 , 48 , 50 , 53 , 54 , 56 ].…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…Given the pluses and minuses of the online/remote didactic activities, the majority (75%) of the participants in this study expressed their belief that the future of dental education will be impacted by the COVID-19 crisis. This is a general belief that has been revealed by many studies [ 9 , 10 , 12 , 23 , 29 , 36 , 42 , 44 , 45 , 46 , 48 , 50 , 53 , 54 , 56 ].…”
Section: Discussionmentioning
confidence: 81%
“…Another question with a high frequency of answers, this time towards the unfavorable end of the scale, is about the remaining online teaching methods after the end of the pandemic period. This clear negative reaction was caused not only by the difficulties posed by the new online teaching method and the new tools that have to be used, but also by the fact that without direct contact with patients and without hands-on practice, the quality of the educational process will significantly decrease [ 11 , 12 , 36 , 43 , 52 , 53 ]. In this regard, the biggest challenge for lecturers and professors has been to compensate for the lack of clinical training, and to re-invent and re-adapt the educational process in a very short period of time, without any previous preparation or planning, and while also constrained by distance, legal and ethical problems (such as the use of “show and share” patient clinical pictures in digital environment) [ 23 , 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…Many studies on virtual education have observed an increase in students' stress levels in virtual education (20,21). However, the students did not report this issue.…”
Section: Discussionmentioning
confidence: 84%
“…The participants were complaining about distractions due to internet quality and connectivity. Dental students in other countries also faced challenges with inadequate hardware, limited bandwidth, and unstable internet connections, all of which posed potential obstacles for online courses [18,19]. However, distance education offers students a flexible, independent, and easily accessible learning setting [19].…”
Section: Resultsmentioning
confidence: 99%
“…Dental students in other countries also faced challenges with inadequate hardware, limited bandwidth, and unstable internet connections, all of which posed potential obstacles for online courses [18,19]. However, distance education offers students a flexible, independent, and easily accessible learning setting [19]. Research showed that dental students believed that distance learning served as an effective alternative during the COVID-19 pandemic and that they expressed a desire to continue with distance learning in the future [4].…”
Section: Resultsmentioning
confidence: 99%